Spatio-temporal dynamics of automatic processing of phonological information in visual words - Wang, Xiao-Dong (2014)
Sensory-specific cortices appear to be sensitive to information from another modality. Here we investigate whether the human brain automatically extracts the phonological information in visual words in early visual processing. We continuously presented native Chinese speakers peripherally with Chinese homophone characters in an oddball paradigm, while they performed a visual detection task presented in the centre of the visual field. We found the lexical tone phonology embedded in the characters is processed automatically by the brain of native speakers, as revealed by whole-head electrical recordings of the mismatch negativity (MMN). Source solution further revealed the MMN involved the neural activations from the visual cortex to the auditory cortex (130–460 ms). The spatial-temporal dynamics indicate a visual-auditory interaction in the early, automatic processing of phonological information in visual words.